Fluid evolution and fragmentation characteristics under high pressure water jet impact on thermal rock - Jianming Shangguan; Zhaolong Ge; Qinglin Deng; Yuhuai Cui; Zhi Yao (International Journal of Mining Science and Technology)
In the application of high-pressure water jet assisted breaking of deep underground rock engineering, the influence mechanism of rock temperature on the rock fragmentation process under jet action is still unclear. Therefore, the fluid evolution characteristics and rock fracture behavior during jet impingement were studied. The results indicate that the breaking process of high-temperature rock by jet impact can be divided into four stages: initial fluid-solid contact stage, intense thermal exchange stage, perforation and fracturing stage, and crack propagation and penetration stage. With the increase of rock temperature, the jet reflection angles and the time required for complete cooling of the impact surface significantly decrease, while the number of cracks and crack propagation rate significantly increase, and the rock breaking critical time is shortened by up to 34.5%. Based on numerical simulation results, it was found that the center temperature of granite at 400 °C rapidly decreased from 390 to 260 °C within 0.7 s under jet impact. In addition, a critical temperature and critical heat flux prediction model considering the staged breaking of hot rocks was established. These findings provide valuable insights to guide the water jet technology assisted deep ground hot rock excavation project.